The Influence of the Use Artificial Intelligence (AI) Based Media on Critical Thinking Skills and Writing Skills of Expository Texts of Class X Students - Magvira, Magvira; Sultan, Sultan; Nensilianti, Nensilianti (FKIP - Universitas Riau, 2025)
The purpose of the study was to prove the significant effect of the use of Artificial Intelligence (AI)-based media on critical thinking skills and exposition text writing skills of class X students of UPT SMA Negeri 4 Luwu. This study used a true experimental design with a pretest-posttest control group design model. All class X students of UPT SMA Negeri 4 Luwu were the population in this study. Data collection techniques through written tests before and after treatment. The results of the analysis indicate that there is a significant effect of the use of Artificial Intelligence (AI)-based media on students' critical thinking skills. The results of the Paired Sample T Test show = 30.668 > = 2.013 with a Sig. value. (2-tailed) = 0.000 < 0.05 so that H₁ is accepted. The average critical thinking ability increased from 47.13 (low category) to 75.96 (high category). The use of Artificial Intelligence media also has a significant effect on students' exposition text writing skills. The results of the Paired Sample T Test show = 8.935 > = 2.013 with a Sig. value. (2-tailed) = 0.000 < 0.05 so that H₁ is accepted. The average writing skills increased from 58.94 (less category) to 76.38 (sufficient category).